Suksesi Bisnis Keluarga/Bisnis Kecil dan Keberhasilan Bisnisnya - Tuhardjo, Tuhardjo (Jurnal Aplikasi Manajemen, 2011)
A familly or small business as one in which both ownership and policy making are dominated by members of an "emotional kinship group". This characteristic results in a number of operational differences between family/small business and other firms. Chief among these differences is the manner in which family/small businesses handle succession from one generation to the next. To become successful, one of task for leader is plan for "business successsion" to the next generation.